Integration of comparative transcriptomics and WGCNA characterizes the regulation of anthocyanin biosynthesis in mung bean (Vigna radiata L.) - Li, Chunxia; Gao, Zexiang; Hu, Weili; Zhu, Xu; Li, Youjun; Li, Na; Ma, Chao (Frontiers in Plant Science, 2023)
Mung bean is a dual-use crop widely cultivated in Southeast Asia as a food and medicine resource. The development of new functional mung bean varieties demands identifying new genes regulating anthocyanidin synthesis and investigating their molecular mechanism. In this study, we used high-throughput sequencing technology to generate transcriptome sequence of leaves, petioles, and hypocotyls for investigating the anthocyanins accumulation in common mung bean variety as well as anthocyanidin rich mung bean variety, and to elucidate their molecular mechanisms. 29 kinds of anthocyanin compounds were identified. Most of the anthocyanin components contents were significantly higher in ZL23 compare with AL12. Transcriptome analysis suggested that a total of 93 structural genes encoding the anthocyanin biosynthetic pathway and 273 regulatory genes encoding the ternary complex of MYB-bHLH-WD40 were identified, of which 26 and 78 were differentially expressed in the two varieties. Weighted gene co-expression network analysis revealed that VrMYB3 and VrMYB90 might have enhanced mung bean anthocyanin content by inducing the expression of structural genes such as PAL, 4CL, F3'5'H, LDOX, and F3'H, which was consistent with qRT-PCR results. These findings are envisaged to provide a reference for studying the molecular mechanism of anthocyanin accumulation in mung beans. KEYWORDS Mung bean, anthocyanins, transcriptome sequencing, weighted gene co-expression analysis, differentially expressed genes 1 IntroductionMung bean (Vigna radiata L.) is a cowpea (Vigna) plant belonging to the leguminosae family and is one of the fastest-growing edible legume crops in Asia (Zhao et al., 2022; Han et al., 2021). Not only is it drought-and infertile-resistant, and easy to cultivate, it can also symbiotically fix nitrogen, making it a better alternative to cereals, sweet potatoes, cotton and other fruit trees.